1997
DOI: 10.1243/0309324971513355
|View full text |Cite
|
Sign up to set email alerts
|

A parametric study of the elastic stress distribution in pin-loaded tubes

Abstract: This paper describes a numerical study of the stress distribution in pin-loaded tubes. The effects of (a) the distance from the pin to the open end, (b) the variation in pin diameter, (c) the variation of tube thickness and (d) the variation in pin fit on the radial and circumferential stresses around the pin hole have been found and discussed. It is found that there are considerable differences between the stresses at the inner and outer surfaces of the tube which arise because the region around the pin and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 3 publications
3
19
0
Order By: Relevance
“…These effects and the general trend are echoed in photoelastic work by Heywood [4], in photoelastic work on tubes by Ahmad and Stanley [7], and in numerical work, again on tubes, by Grant and Smart [2]. When changing from a snug-to an interference-fitting pin, large variations in the position and the magnitude of the circumferential stresses are documented [1,2]. For a joint subject to fatigue loading, the beneficial effects of an interference fit are commented upon; here, it is reported that this leads to a reduction in the alternating circumferential stresses around the pin hole.…”
Section: Literature Reviewmentioning
confidence: 90%
See 4 more Smart Citations
“…These effects and the general trend are echoed in photoelastic work by Heywood [4], in photoelastic work on tubes by Ahmad and Stanley [7], and in numerical work, again on tubes, by Grant and Smart [2]. When changing from a snug-to an interference-fitting pin, large variations in the position and the magnitude of the circumferential stresses are documented [1,2]. For a joint subject to fatigue loading, the beneficial effects of an interference fit are commented upon; here, it is reported that this leads to a reduction in the alternating circumferential stresses around the pin hole.…”
Section: Literature Reviewmentioning
confidence: 90%
“…6 Two-dimensional variation in s r around the lug hole for an interference fit by loading increments of 20 per cent of P the hole and causes distinct changes in the position of the maximum circumferential stress, although, away from a snug fit, the stresses are not sensitive to the value of the clearance. These effects and the general trend are echoed in photoelastic work by Heywood [4], in photoelastic work on tubes by Ahmad and Stanley [7], and in numerical work, again on tubes, by Grant and Smart [2]. When changing from a snug-to an interference-fitting pin, large variations in the position and the magnitude of the circumferential stresses are documented [1,2].…”
Section: Literature Reviewmentioning
confidence: 93%
See 3 more Smart Citations